Analisis Kepuasan Pengguna Terhadap Penerapan Aplikasi Tokopedia dengan Menggunakan Metode TAM - Taufik Hidayat; Dilla Selika Canta (JURIKOM (Jurnal Riset Komputer), 2022)
Tokopedia is one of the largest online marketplace providers in Indonesia that facilitates internet users to conduct online buying and selling activities. However, based on a survey conducted by TOP Brand, Tokopedia was ranked first in 2021 with a score of 4.53%. Tokopedia is ranked 1st as the best e-commerce site in Indonesia. This will certainly be a matter of concern for managers from Tokopedia to improve the quality of service on their website. Because the quality of this service is the key to measuring customer satisfaction. This study aims to determine user satisfaction with the Tokopedia application for international Borneo STMIC students, Balikpapan. The model used to explain user satisfaction with the application of the Tokopedia application is the Technology Acceptance Model (TAM) with 5 constructs. close that the use of the Tokopedia application (actual use) with a percentage of 86.07%, the ease of the Tokopedia application (perceived easy of use) with a percentage of 86.78%, the benefits of the Tokopedia application (perceived usefulness) with a percentage value of 86.78%, the risk of the Tokopedia application (perceived risk) with a percentage value of 86.60% and the trust of Tokopedia application users (trust) with a percentage value of 87.32% with the category strongly agree. From the results of perceived satisfaction, it can be stated that STMIK BI Balikpapan students are satisfied in using the Tokopedia application.